(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Pediatric brain tumors represent the most common solid malignancies in children and remain a major cause of cancer-related morbidity and mortality in the pediatric population. Despite advances in neurosurgical techniques, molecular diagnostics, and adjuvant therapies, treatment outcomes remain highly variable depending on tumor type, grade, and anatomical location. Recent developments in molecular profiling, intraoperative neuroimaging, and targeted therapies have transformed the diagnostic and therapeutic landscape of pediatric neuro-oncology. This paper reviews current challenges in the management of pediatric brain tumors, including delayed diagnosis, surgical limitations, and treatment-related neurocognitive sequelae, while also highlighting recent innovations such as precision medicine, proton beam therapy, and neurosurgical navigation systems. Multidisciplinary collaboration and translational research remain critical to improving long-term survival and quality of life in affected children.